2016
DOI: 10.1109/tie.2016.2594038
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Modulation Scheme for Dual-Output Five-Leg Indirect Matrix Converter

Abstract: Abstract-this paper proposes a hybrid modulation method for a dual-output five-leg indirect matrix converter topology. The proposed control technique combines a space vector modulation scheme (SVPWM) applied to the rectifier stage so as to control the input currents and a new digital scalar modulation scheme (DSPWM) designed to control the two loads output voltages. A generalized expression of the output voltage references is also developed showing the capability of the proposed method to control more than two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Depending on the operational modes, these currents could have different specifications as summarized in Table 4. Since the stator and rotor side ports experience different frequencies, the maximum current that should be selected for the current rating of the bottom and top switches is equal to I smax + I rmax [35], [36].…”
Section: B Power Switching Ratingmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the operational modes, these currents could have different specifications as summarized in Table 4. Since the stator and rotor side ports experience different frequencies, the maximum current that should be selected for the current rating of the bottom and top switches is equal to I smax + I rmax [35], [36].…”
Section: B Power Switching Ratingmentioning
confidence: 99%
“…Considering same specifications for switches in different topologies, the conduction loss is proportional to the instantaneous current flowing through the switches [35], [36]. For BB converter, the instantaneous currents of the upper and lower ports are related to the currents of stator and rotor windings.…”
Section: Loss Comparisonmentioning
confidence: 99%
“…Reducing the number of switching devices is desirable; therefore, many research results have shown simplified configurations for DMDS. For example, a reduced-switch-count inverter [1][2][3], a nine-switch inverter [4][5][6][7], a mono inverter [8][9][10], a five-leg inverter [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…There are several control methods for driving dual motors using FLI [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The similarity of these control methods is that the sum of the output voltages supplied to the dual motors is limited to the DC-link voltage.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim to avoid the connecting of DC bus capacitors, five-leg power converter (FLC) topologies with a common leg have been adopted by connecting the three-phase machine through three TRIACs to the phases of a similar three-phase grid [20][21][22][23][24][25]. Similar converter topologies were addressed in [26][27][28][29][30][31][32][33] by connecting symmetrical legs in multimotor drives. Apart from the aforementioned advantage, these topologies can be easily implemented and require fewer devices (only three TRIACs).…”
mentioning
confidence: 99%